Chronic diffuse infiltrative lung disease (CDILD) : A comparative study between high resolution computed tomography (HRCT) and lung ultrasound (LUS) - Shereen Mohamed Abdelraouf Khalil; Hatem Said Elazizi; Yasmine Hamdy Elhinawy; YoussriahYahia Sabri (Cairo : Shereen Mohamed Abdelraouf Khalil, 2020)
Lung ultrasound (LUS) is a noninvasive, non-radiating examination and is very sensitive to detect subtle changes in the subpleural space ( Manolescu et al. ,2018).At the start of ILD, pleural irregularities are most often in the lower fields of the lungs and progressively there is a spreading in middles and upper fields of the lungs with the progression of ILD( Buda et al. ,2016)( Falcetta et al. ,2018).The evidence of diffuse, multiple B-lines defined as vertical, hyperechoic artifacts is the hallmark of interstitial lung disease . A thick, irregular, fragmented pleura line is associated with subpleural fibrotic scars. The distribution of the LUS artifacts has a diagnostic value (Manolescu et al.,2018).To assess the pleural and parenchymal findings, the sonograms were analyzed for (1) existence of comet tail artifacts (B-lines), (2) a thickened pleural line, (3) an irregular, fragmented pleural line, and (4) echogenic
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Rradio-Diagnosis
Issued also as CD
Keywords: High resolution computed tomography (HRCT); Lung Disease (CDILD); Lung ultrasound (LUS)